Edukasi Area Privasi Tubuh Melalui Program Area Amanku Bagi Siswa SD Negeri 2 Jatipuro - Shifa Puspitasari; Septiati Septiati; Novia Rista Ramadhani; Fairuz Sakha Hanun Zain Aribah; Sintia Devi Astuti Dwi Cahyani; Cindy Dwi Widyastuti; Najma Adiba; Apriliya Wulandari; Raihan Syafa Yunanto; Akid Sinatriya Wiratama; Achmad Muchibbin (Amirul Bangun Bangsa, 2026)
Program